Modified flow- and oxygen-related autoregulation indices for continuous monitoring of cerebral autoregulation - Hecht, Nils Nicholas; Fiss, Ingo; Wolf, Stefan; Barth, Martin; Vajkoczy, Peter; Woitzik, Johannes (Journal of neuroscience methods, 2011)
Continuous monitoring of brain tissue partial pressure of oxygen (ptiO2), thermal-diffusion regional cerebral blood flow (TD-rCBF) and cerebral perfusion pressure (CPP) allows the calculation of flow- and oxygen-related autoregulation indices ORx and FRx. The influence of temporal phase shifts on ORx and FRx due to a delay in the response time of ptiO2 and TD-rCBF has received little attention. We investigated the impact of phase shifts between changes in CPP and the corresponding ptiO2 and TD-rCBF responses on the degree of correlation of ORx and FRx. In five patients with aneurysmal subarachnoid hemorrhage continuous multimodal neuromonitoring was performed for 7-10 days. In each patient the phase shift of the ptiO2- and TD-rCBF-response after spontaneous positive or negative CPP fluctuations during two 1-h time periods of disturbed cerebral autoregulation was determined. For these periods, ORx and FRx were calculated as Pearson correlation coefficients before (ORx and FRx) and after (ORxsync and FRxsync) temporal synchronization of ptiO2, TD-rCBF and CPP. The mean temporal phase shift after CPP fluctuations was 65±11s for ptiO2 and 12±4s for TD-rCBF. Before synchronization, ORx and FRx were determined at 0.52±0.3 and 0.59±0.3, respectively. After synchronization, ORxsync and FRxsync correlated significantly stronger than unsynchronized indices (ORxsync: 0.66±0.3; FRxsync: 0.62±0.3; p<0.01 vs. ORx and FRx, respectively). These findings suggest that ORx and FRx are subject to temporal latency shifts of ptiO2 and TD-rCBF in regard to spontaneous CPP fluctuations. Temporal synchronization for the calculation of both ORx and FRx may permit continuous monitoring of these indices with higher sensitivity.
Gesehen am 28.09.2022